Creating a Superiorly Based Pharyngeal Flap: Is Prominence of C1 Superior Enough, and Will Adenoid Pad Be in the Way? - Thomas J. Sitzman, MD, MPH; Jessica L. Chee-Williams, MS; Taylor D. Snodgrass, MS; Imani R. Gilbert, MS; Travis T. Tollefson, MD, MPH; Davinder J. Singh, MD; Jamie L. Perry, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Positioning the pharyngeal flap base high along the posterior pharyngeal wall is essential for optimizing speech outcomes. Objective data on where to place the flap base are lacking. Further, adenoid tissue can restrict cephalad positioning of the flap. This study aimed to improve the design of the pharyngeal flap by measuring the distance from the first cervical vertebrae (C1) to the palatal plane, and the adenoid depth in children undergoing evaluation for velopharyngeal insufficiency. Methods:. This retrospective cross-sectional study analyzed magnetic resonance imaging (MRI) scans of the velopharynx and measured the distance between C1 and the palatal plane, and the adenoid depth at the level of the palatal plane in millimeters. Results:. Thirty-four patients met the inclusion criteria. The mean age at the time of MRI was 7.4 years (range: 3.9–11.9 y). The anterior tubercle of C1 was below the palatal plane in 97% (n = 33) of patients. On average, this landmark was 10.5 mm (SD = 5.0) below the palatal plane. Adenoid tissue was present at the level of the palatal plane in 91% (n = 31) of patients. Conclusions:. Positioning the pharyngeal flap base at C1 is too low to aid with velopharyngeal closure. Further, adenoid tissue is frequently present at the level of velopharyngeal closure, limiting superior positioning of the pharyngeal flap base. When this occurs, surgeons should consider adenoidectomy before pharyngeal flap surgery. Preoperative MRI may be beneficial for planning pharyngeal flap positioning relative to C1 and assessing adenoid tissue at the palatal plane.